DYNAMICS OF THE GENETIC STRUCTURE OF THE KRASNODAR GREENBUG POPULATION UNDER HOST PLANT ALTERATION - E. E. Radchenko; T. L. Kuznetsova; N. V. Alpatieva (Вавиловский журнал генетики и селекции)
A high level of overall and seasonal variabilityof the Krasnodar greenbug population for virulence to sorghum and barleyresistance genes as well for RAPD markers was revealed. The selection of insectgenotypes specificallyadapted to hostplantspecies was recorded. Aphid clones avirulentto resistantsorghum accessions were mostabundanton the barley. Greenbug migration from barleyto sorghum led to rapid accumulation of clones virulentto sorghum genes for resistance: Sgr1– Sgr4 and Sgr12. After alteration of the host, a significantshiftof genotype groups similar in RAPD profiles was observed. The distribution of RAPD markers was independentof alleles for virulence of the aphid.